Pengaruh Profitabilitas, Likuiditas dan Leverage Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek indonesia Periode 2015-2021 - Baiq Ninis Tridara; Iwan Kusmayadi; Iwan Kusuma Negara (Journal of Sharia Economy and Islamic Tourism, 2024)
This study aims to empirically examine the Effect of Profitability, Liquidity and Leverage on Dividend Policy in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2015-2019 Period. This study uses the Dividend Payout Ratio (DPR) as the dependent variable, as well as Return on Assets (ROA), Current Ratio (CR) and Debt to Equity Ratio (DER) as independent variables. This research is associative and the type of data used in this study is quantitative data because the research aims to determine the effect of two or more variables. The population in this study are 27 companies listed on the food and beverage sub-sector manufacturing companies on the Indonesia Stock Exchange. Sampling in this study using purposive sampling method with certain criteria, based on predetermined criteria obtained a sample of 7 companies. The analytical method in this study uses multiple linear regression analysis techniques. The results showed that Profitability (ROA) had a negative and insignificant effect on dividend policy, Liquidity (CR) had a positive and insignificant effect on dividend policy and Leverage (DER) had a negative and significant effect on dividend policy.